Achados clínicos, microscópicos e imunoistoquímicos dos carcinomas espinocelulares orais convencionais comparados aos de orofaringe: revisão integrativa da literatura - Santos, Raquel Vieira dos (2022)
Squamous cell carcinoma (SCC) accounts for about 90% of oral cavity neoplasms. Oropharyngeal cancer has been increasing over the last 20 years in high-income countries along with the decline in smoking and the increase in human papillomavirus (HPV) infection. SCC associated with HPV is usually located in the oropharynx, presenting different characteristics from conventional HPV-negative SCC. Scientific studies that characterize the morphological and immunohistochemical profile of the SCC are relevant, especially when compared to those located in the oropharynx. This study aims to explore the morphological and immunohistochemical aspects of conventional oral squamous cell carcinomas compared to oropharyngeal carcinomas, as well as their clinical and prognostic implications. A search for scientific studies was carried out in PubMed and Scopus databases using MeSH strategy terms and keywords, later the studies were included in the Rayyan reference manager for their selection. A total of 452 studies were selected in the title and abstract reading phase, 31 were obtained for full text reading, of which 16 were included in this review. According to the protocol of the Joanna Briggs Institute, in the evaluation of the quality of the studies, studies with low risk of bias were predominant, being these in 12, another 03 with moderate and 01 with high risk. The main location was in the oral cavity, histologically a fibrotic stroma was identified, cells containing expressions in the cytoplasm region, basement and intermediate membrane and immunoreactivity increase according to the increase in histological grade or proximity to the tumor. p16 in tumor tissue showed a favorable molecular phenotype. The expression of p16 does not represent HPV infection, however it was acceptable as a surrogate prognostic marker for HPV-associated oropharyngeal SCC. It was related to lower staging for well and moderately differentiated graduation. Immunohistochemistry is relevant for collaboration in the diagnosis and prognosis of oral and oropharyngeal SCC, such as the use of markers such as p16, HSP-27, TLR4, MT1-MMP, Kif5b, PMS2, JAG2, TKs4, TKs5 and CD44v6 to establish a better patient management.